Curves for the estimation of the moisture content of ten hardwoods by means of electrical resistance measurements - Fernandez-Golfin, J. I.; Conde, M.; Conde, M.; Fernandez-Golfin, J. J.; Calvo, R.; Baonza, M. V.; de Palacios y Palacios, P. (Forest Systems, 2012)
Accuracy in moisture content measurement is of great importance in the assurance of wood product quality and isnecessary to meet administrative and normative requirements. Improving the accuracy of resistance-type moisture meters,and meeting the normative demands of their annual calibration, requires the use of optimised curves relating electricalresistance to moisture content for the most commercially important wood types. The Samuelsson model, adjusted bylinear regression techniques, was used to describe the relationship between the electrical resistance and moisture contentof seven boreal and three tropical hardwoods available on the Spanish market. The curves produced can be used to predictthe moisture contents of these hardwoods via the measurement of their electrical resistance with an error of just ± 1.0%.These curves should also prove of great use in the calibration of wood resistance-type moisture meters.